Corporate governance dan accounting conservatism di Industri Perbankan Indonesia - Agung Nurmansyah (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2022)
Bank managers are very important in implementing the governance of a bank. Implementing governance will affect accounting conservatism. Tujaun of this research is to evaluate the corporate governance factors that affect the level of accounting conservatism in the bank's financial statements exposed on the Indonesia stock exchange. The sample used were 25 big banks. This research uses multiple regesi analysis tools. The results of the research are managerial ownership, institutional ownership, audit committees and self assessment of good corporate governance affecting accounting conservatism. The independent board of commissioners has no effect on accounting conservatism. To increase the conservatism of accounting factors managerial ownership becomes an important factor in corporate governance.